2019
DOI: 10.1002/dc.24146
|View full text |Cite
|
Sign up to set email alerts
|

Cytological diagnosis of papillary thyroid carcinoma with tall cells on ThinPrep liquid‐based cytology

Abstract: Background The tall cell variant of papillary thyroid carcinoma (PTC‐TC) has been associated with aggressive features including extrathyroidal extension, higher rate of lymph node and distant metastases, and higher recurrence rate. We aimed to evaluate the cytomorphologic features of PTC‐TC on ThinPrep (TP) along with its diagnostic efficacy to detect PTC‐TC. Methods Preoperative cytology samples from 30 cases of histologically‐proven PTC‐TC and 30 classical PTC controls were selected for this study. TP prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…In our study, psammoma bodies were found in only 11 (5.0%) of 222 liquid-based cytology specimens. Tall cells are easily identified in liquid-based preparations and their presence in FNAC was strongly correlated with tall cell variants of PTC [14,26]. However, there was no association between tall cells and lymph node metastasis in our present and previous studies [18].…”
Section: Discussioncontrasting
confidence: 62%
“…In our study, psammoma bodies were found in only 11 (5.0%) of 222 liquid-based cytology specimens. Tall cells are easily identified in liquid-based preparations and their presence in FNAC was strongly correlated with tall cell variants of PTC [14,26]. However, there was no association between tall cells and lymph node metastasis in our present and previous studies [18].…”
Section: Discussioncontrasting
confidence: 62%
“…Papillary thyroid carcinoma (PTC) develops slowly, without causing obvious pain during the course of development, and it has a low rate of distant metastasis and death, so many potential patients are only identified postmortem [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Classically for these tumors that are considered as "intermediate risk" according to the ATA, the option of a total thyroidectomy is generally retained. [29][30][31] In particular, the tall-cell variant of PTC is more likely to present with multifocal and bilateral disease, thus the indication becomes more compelling under such circumstances. 32 The removal of all thyroid tissue is justified for most tall-cell and other aggressive variants based on a higher likelihood for ETE.…”
Section: Tumor Characteristicsmentioning
confidence: 99%
“…However, such variants are more often diagnosed on histopathology. Classically for these tumors that are considered as “intermediate risk” according to the ATA, the option of a total thyroidectomy is generally retained 29‐31 . In particular, the tall‐cell variant of PTC is more likely to present with multifocal and bilateral disease, thus the indication becomes more compelling under such circumstances 32 .…”
Section: Decision‐making Process In the Staged Thyroidectomy Approachmentioning
confidence: 99%